Konteks Sosiocultural Practice pada Lagu “Oras Loron Malirin” (Analisis Wacana Kritis Norman Fairclough) - Rozario Mendonca Da Costa (Concept: Journal of Social Humanities and Education, 2023)
This research is entitled The context of sociocultural practice in the song "Oras Loron Malirin" with Norman Fairclough's study. The issues discussed were (3) How is the sociocultural practice in the song "Oras Loron Malirin"? The type of research in this study is to use a descriptive qualitative research approach with Norman Fairclough's critical discourse analysis model. The type of data used in this study is a song text entitled "Oras Loron Malirin" and the data source in this study is the subject from which the data was obtained. The data source is the lyrics of the song "Oras Loron Malirin" which comes from the Belu area of ​​East Nusa Tenggara Province. In this study, researchers used data collection techniques in the form of documentation techniques. The data analysis technique used in examining this research is descriptive data analysis techniques according to Miles and Huberman, namely, reduction, data display, and conclusion drawing / verification. The results of this study are in the form of data in the analysis of sociocultural practice, there are several things, namely cultural systems, economic systems and political systems that greatly influence the development of a discourse.